Human Resource Management Based on Sharia: How Employees Determine Sharia Law in the Context of Islamic Finance (Case Study: Bank Syariah Indonesia in Malang City, East Java) - Ragil, Bambang; Purnomo, Eko Priyo; Hadiyati, Ernani (Jurnal Manajemen Teknologi, 2024)
Abstract. This research explores employee perceptions of Sharia principles in the context of Human Resource Management (HRM) at Bank Syariah Indonesia in Malang City, East Java. The study employs a case study design with a qualitative approach, chosen for its ability to provide an in-depth understanding of how employees perceive and apply Sharia principles within the framework of Sharia-oriented HRM at the bank. Data were collected through in-depth interviews, direct observation, and document analysis involving a purposive sample of 15 employees from various positions within the bank, including staff and managers, with diverse lengths of service and demographic characteristics. The findings suggest that education and training focused on Sharia principles are crucial in shaping employees' understanding and attitudes. Additionally, a Shariah-oriented organizational culture positively influences employee behaviors and attitudes, aligning them more closely with the institution's values. These results offer practical implications for Islamic financial institutions, emphasizing the need to strengthen educational programs and enhance organizational culture to foster Sharia-compliant human resources. Furthermore, the study highlights opportunities for better employee development, particularly in developing technical skills and integrating Islamic ethical values. In conclusion, this research significantly contributes to the literature on Islamic-oriented HRM and provides valuable insights for practitioners and researchers in the field. Keywords: Human Resource Management (HRM), sharia principles, employee perception, islamic finance   Abstrak. Penelitian ini mengeksplorasi persepsi karyawan terhadap prinsip-prinsip Syariah dalam konteks Manajemen Sumber Daya Manusia (MSDM) di Bank Syariah Indonesia di Kota Malang, Jawa Timur. Penelitian ini menggunakan desain studi kasus dengan pendekatan kualitatif, yang dipilih karena kemampuannya untuk memberikan pemahaman yang mendalam tentang bagaimana karyawan memandang dan menerapkan prinsip-prinsip Syariah dalam kerangka kerja MSDM yang berorientasi Syariah di bank tersebut. Data dikumpulkan melalui wawancara mendalam, observasi langsung, dan analisis dokumen yang melibatkan sampel purposif sebanyak 15 karyawan dari berbagai posisi di bank, termasuk staf dan manajer, dengan masa kerja dan karakteristik demografis yang beragam. Temuan menunjukkan bahwa pendidikan dan pelatihan yang berfokus pada prinsip-prinsip Syariah sangat penting dalam membentuk pemahaman dan sikap karyawan. Selain itu, budaya organisasi yang berorientasi pada Syariah secara positif mempengaruhi perilaku dan sikap karyawan, menyelaraskan mereka lebih dekat dengan nilai-nilai institusi. Hasil penelitian ini memberikan implikasi praktis bagi lembaga keuangan syariah, yang menekankan perlunya memperkuat program pendidikan dan meningkatkan budaya organisasi untuk membina sumber daya manusia yang patuh terhadap Syariah. Selain itu, penelitian ini menyoroti peluang untuk pengembangan karyawan yang lebih baik, terutama dalam mengembangkan keterampilan teknis dan mengintegrasikan nilai-nilai etika Islam. Kesimpulannya, penelitian ini memberikan kontribusi yang signifikan terhadap literatur tentang HRM berorientasi Islam dan memberikan wawasan yang berharga bagi para praktisi dan peneliti di lapangan. Kata kunci: Manajemen Sumber Daya Manusia (MSDM), prinsip-prinsip syariah, persepsi karyawan, keuangan syariah